2020
DOI: 10.1177/1179546820953416
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Inferior Lead Q-waveforms in diagnosing Ventricular Tachycardia

Abstract: Background: Electrocardiogram (ECG) differentiation of wide complex tachycardia (WCT) into ventricular tachycardia (VT) and supraventricular tachycardia with aberration (SVT-A) is often challenging. Objective: To determine if the presence of Q-waveforms (QS, Qr, QRs) in the inferior leads (II, III, aVF) can differentiate VT from SVT-A in a WCT compared to Brugada algorithm. We studied 2 inferior lead criteria namely QWC-A where all the inferior leads had a similar Q wave pattern and QWC-B where only lead aVF h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…[ 3 4 ] The Basel algorithm, limb lead algorithm, and inferior lead Q-wave algorithm are the three newer ECG algorithms that have recently been proposed to differentiate VT from SVT in WCT. [ 7 8 9 ] The limitations of current existing algorithms are the complexity of algorithms, less diagnostic accuracy, and the chance of misdiagnosis of preexcited SVT/fascicular VT/wide complex atrial flutter.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 4 ] The Basel algorithm, limb lead algorithm, and inferior lead Q-wave algorithm are the three newer ECG algorithms that have recently been proposed to differentiate VT from SVT in WCT. [ 7 8 9 ] The limitations of current existing algorithms are the complexity of algorithms, less diagnostic accuracy, and the chance of misdiagnosis of preexcited SVT/fascicular VT/wide complex atrial flutter.…”
Section: Discussionmentioning
confidence: 99%
“…One more recent report describes a patient with remote anterior wall myocardial infarction and left bundle branch block where anterior Q‐waves appeared during VT 3 . Subramany et al reported that inferior Q‐waves during WCT—without reference to SR ECG—are specific, but insensitive signs of VT 4 …”
Section: Figurementioning
confidence: 99%
“… 1 Premature ventricular beats have long been shown to uncover pathologic Q‐waves after myocardial infarction that is otherwise not evident on the ECG. 2 One more recent report describes a patient with remote anterior wall myocardial infarction and left bundle branch block where anterior Q‐waves appeared during VT. 3 Subramany et al reported that inferior Q‐waves during WCT—without reference to SR ECG—are specific, but insensitive signs of VT. 4 …”
mentioning
confidence: 99%